Synthesis of N-acetyl-d-quinovosamine in Rhizobium etli CE3 is completed after its 4-keto-precursor is linked to a carrier lipid - Li, Tiezheng (Microbiology (Reading), 2017)
Bacterial O-antigens are synthesized on lipid carriers before being transferred to lipopolysaccharide core structures. Rhizobium etli CE3 lipopolysaccharide is a model for understanding O-antigen biological function. CE3 O-antigen structure and genetics are known. However, proposed enzymology for CE3 O-antigen synthesis has been examined very little in vitro, and even the sugar added to begin the synthesis is uncertain. A model based on mutagenesis studies predicts that 2-acetamido-2,6-dideoxy-d-glucose (QuiNAc) is the first O-antigen sugar and that genes wreV, wreQ and wreU direct QuiNAc synthesis and O-antigen initiation. Previously, synthesis of UDP-QuiNAc was shown to occur in vitro with a WreV orthologue (4,6-hexose dehydratase) and WreQ (4-reductase), but the WreQ catalysis in this conventional deoxyhexose-synthesis pathway was very slow. This seeming deficiency was explained in the present study after WreU transferase activity was examined in vitro. Results fit the prediction that WreU transfers sugar-1-phosphate to bactoprenyl phosphate (BpP) to initiate O-antigen synthesis. Interestingly, WreU demonstrated much higher activity using the product of the WreV catalysis [UDP-4-keto-6-deoxy-GlcNAc (UDP-KdgNAc)] as the sugar-phosphate donor than using UDP-QuiNAc. Furthermore, the WreQ catalysis with WreU-generated BpPP-KdgNAc as the substrate was orders of magnitude faster than with UDP-KdgNAc. The inferred product BpPP-QuiNAc reacted as an acceptor substrate in an in vitro assay for addition of the second O-antigen sugar, mannose. These results imply a novel pathway for 6-deoxyhexose synthesis that may be commonly utilized by bacteria when QuiNAc is the first sugar of a polysaccharide or oligosaccharide repeat unit: UDP-GlcNAc → UDP-KdgNAc → BpPP-KdgNAc → BpPP-QuiNAc.